Proposed Warehouse Layout Improvement for Optimizing Travel Distance and Material Handling Costs Using the ABC Method at PT X - Agi Agus Setiawan Sufyan; Yayan Mulyana; Ilham Eka Santang; Afriani Kusumadewi (Justek : Jurnal Sains dan Teknologi, 2026)
The research employed a quantitative descriptive approach using warehouse operational data, including picking frequency, rack coordinates, and material movement information. Inventory items were classified into three categories—Class A (fast-moving), Class B (medium-moving), and Class C (slow-moving)—based on usage frequency. Subsequently, warehouse rack positions were rearranged according to ABC priorities, followed by recalculation of travel distances and material handling costs. The findings indicate that the proposed warehouse layout significantly improves operational efficiency for frequently moved products. The total travel distance for Class A items decreased from 1,662 meters to 1,272 meters, representing a reduction of 23%, while Class B items decreased from 807 meters to 771 meters, equivalent to a 4% reduction. Consequently, material handling costs for Class A and Class B movements also decreased proportionally. Although Class C travel distance increased from 279 meters to 705 meters, this change is considered acceptable because slow-moving items contribute minimally to warehouse movement frequency. The study concludes that integrating ABC classification with Rectilinear distance measurement effectively optimizes warehouse layout by reducing travel distance and material handling costs while improving storage efficiency for high-frequency inventory.